Career Adaptability in Special Educational Needs Populations: A Systematic Review of the Empirical Evidence and Emerging Research Directions - Cheng Li; Lan Yang; Kuen Fung Sin; Fengzhan Gao; Alessandra Romano (Behavioral Sciences)
Despite robust evidence linking career adaptability (CA) to positive vocational and psychosocial outcomes in general populations, research on the CA among individuals with special educational needs (SEN) remains limited. Prior reviews have largely overlooked the distinct challenges faced by SEN populations. To address this gap, we conducted a systematic review across five major databases, yielding an initial pool of 81 studies. Following rigorous screening, only eight quantitative studies met the inclusion criteria, reflecting the early stage of the research in this area. The included studies span diverse SEN groups, including individuals with visual impairments, intellectual disabilities, and mental health conditions. CA was consistently found to be associated with adaptive outcomes such as self-esteem, self-efficacy, hope, and career satisfaction. However, the literature is characterized by methodological limitations, notably the predominance of cross-sectional designs, the underrepresentation of neurodevelopmental conditions (e.g., ASD, ADHD), and a lack of cross-cultural perspectives and standardized instruments specifically adapted to SEN learners. Future studies should focus on the need for longitudinal and mixed-method designs, contextually cross-cultural research, and inclusive measurement tools. Furthermore, exploring the ecological and emotional predictors of CA; expanding to underrepresented SEN subgroups; and evaluating diverse interventions beyond mentoring are essential to informing tailored educational and vocational support for individuals with SEN.